Editorial Vol.6(3) - Ahmed, Tahera (Bangladesh Journal of Bioethics, 2015)
Dear Readers, Welcome to this issue of our beloved Bangladesh Journal of Bioethics! In this sweltering heat we are all seeking for some cool and comfort. We bring this issue of BJB on different ethical practices and bring up related questions. Are we respecting the rights of every human being when we are either doing research or practicing health service provision? What are the minimum norms and standards to be maintained or are we circumventing those? The issue looks into different issues and provides us with indepth information, queries, fears and reservations. In the article on Knowledge, attitude and practice of medical ethics among medical intern students in a Medical College in Kathmandu, Ramesh P Aacharyaand Yagya L Shakya , report on a Knowledge Attitude and Practice survey of 46 medical undergraduate interns of Maharajgunj Medical Campus. The result of the survey is quite interesting. Doctors know the best irrespective of patients opinion was agreed upon by 35 %, Confidentiality cannot be kept in modern era and should be abandoned was strongly disagreed by 34.8% and disagreed by 60.9%. The Authors hope that the findings will assist the faculties to strengthen the teaching of medical ethics and guiding the interns for ethical professional conduct. In the article titled Organizational Justice and Employees Service Behavior in the Healthcare Organizations in Bangladesh is an agenda for Research, Md. Nuruzzaman and Md. Humayun Kabir Talukder present a conceptual framework and a set of hypotheses regarding the relationships among distributive justice, procedural justice, interactional justice, employees citizenship behaviour, role prescribed behaviour and counterproductive behavior in the healthcare organizations in Bangladesh. The authors state that the purpose is to assist the policy makers and service providers in identifying desirable and undesirable HRM practices in order to maintain optimum level of employee commitment for ensuring quality and efficient service delivery to the communities. Though the article is theoretical it may be useful for the policy makers and service providers. If an operational research could be carried out to test the hypothesis the practical utility of the concept could be tested in Bangladesh. Zoheb Rafique in the article Ethical Justification of Conducting Research Trials in Lower and Middle Income Countries Including Pakistan: The Responsibilities of Research Enterprises explores the ethical aspects of research sponsored by commercial agencies. He looks into the factors that influence selection of a study site for a sponsored trial particularly in traditional countries like Pakistan where cultural values add to the problem in assuring that research is conducted in an ethical manner. In this paper, the Author discusses the responsibilities of researchers and funders in low and middle income countries like Pakistan and the ethical justifications of doing research trials in developing countries. He concludes that research participants should be fully informed about the research trial and their participation and it is their right to know all risks and benefits so that they have the option of rejecting participation. The article on Ethical aspects of Dhaka University Tele-medicine System by Ahmed Raihan Abir provides and analysis of the tele- medicine system in Dhaka University. The Author is a member of an extended group at Dhaka University (DU) which has been developing telemedicine equipment and data acquisition software to promote telemedicine practice in Bangladesh. Recently the Telemedicine group of DU and a local NGO named SAMAMA with support from Service innovation fund (SIF) of the Prime Minister Office (PMO) of Bangladesh took the initiative to establish eight rural telemedicine centers and one expert center for the field trial of telemedicine in Bangladesh. The aim of this paper is to examine the ethical challenges of such health care system and the effort to overcome these problems before starting the field trial. The author looks into the details of Data confidentiality and security, Responsibilities of Doctor and Rural Technician, Quality of service and Implications of telemedicine in Bangladesh. He concludes that DU telemedicine project will essentially bring the services of qualified medical experts to the doorsteps of the common people throughout the country, even in the remote rural areas. Although a telemedicine cannot match a face to face consultation, DU tele-medicine system is much better than no consultation at all. Sifat Rahman in the article on Ethical Issues of Fair Subject Selection in Research provides an overview of the criterion for maintaining ethical standards for conducting research. The Author reviews the three fundamental conditions to be met for adhering to strict ethical standards which are: Respect for Persons by protecting the autonomy of people, treating them with courtesy and respect and obtaining informed consent.; Beneficence which incorporates the philosophy of "Do no harm" while maximizing benefits for the research project and minimizing risks to the research subjects; and Justice by ensuring that reasonable, non-exploitative, and well-considered procedures are administered fairly. Finally the Author concludes that Researchers must be truthful and conduct no deception. Dear Readers, as you can see from the above ethics and maintaining the values in research and services are of utmost importance in the improvement of the quality of life. Through our queries, questions and sense of respect for every living being can our endeavors to ensure ethics in all spheres of development be successful. Dear Readers, please keep on sending your articles, notes or thoughts to us. Your participation will make a difference in the quality of our lives. Best regards Tahera Ahmed Editor